Pelatihan Kompetensi Komunikasi Pengawas Pemilu di Kabupaten Siak - Moekahar, Fatmawati; Hardianti, Fitri; Daherman, Yudi; Alfani, Mufti Hasan; Pratiwi, Yuly Rahmi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
This service activity aims to provide training to commissioners and employees within the Bawaslu (Badan Pengawas Pemilihan Umum) Siak Regency. As an election supervisor who has the duty and authority as one of the institutions in supervising of all stages of the election, the human resources in it need good communication skills so that the message conveyed through the supervisory action is effective. Therefore, election supervisors must have communication competence as election supervisors. Activities are carried out in the form of training, starting with the presentation of materials and practices of communication competence for election supervisors. All participants participated in the activity enthusiastically. Based on the results of the pretest and posttest, there was an increase in the communication skills of the participants after participating in this communication competency training activity.